Misdirection – Past, Present, and the Future - Kuhn, Gustav; Martinez, Luis M. (Frontiers in Human Neuroscience, 2012)
Misdirection refers to the magician’s ability to manipulate people’s attention, thoughts and memory. It has been argued that some of the techniques used by magicians to orchestrate people’s attention and awareness may provide valuable insights into human cognition. In this paper we review the scientific, as well as some of the magic literature on misdirection. We focus on four main points: 1) the magician's concept of misdirection, 2) the paradigms used to study misdirection scientifically, 3) review of the current scientific findings, and 4) future directions.